Pengenalan Teori Servicescape dan Penerapannya dalam Desain Interior - Ruki, Ulli Aulia (Humaniora, 2011)
The reason of constructing the building facility is to facilitate users? activity and service. The article purpose is to introduce servicescape concept as a part of route that could be used to measure users? satisfaction level towards interior facility by giving additional value in selling goods and services in the building. Servicescape theory is one physical prove that could influence somebody?s point of view about physical environment in a commercial facility. Some points discussed in servicescape are style, design, sign, space layout, function, and ambient condition. Method used is literature study from some books along with illustration analysis related to commercial facility interior. The expected result is to give point of view from servicescape theory that could be applied by an interior design in defining design concept especially related to commercial facility. The conclusion showed some points in servicescape theory that could be used to direct and deliver the designer to design concept decision that would satisfy facility interior users.